POTENTIAL OF REGIONAL BONDS FOR THE DEVELOPMENT OF THE INFRASTRUCTURE OF THE ALTAI TERRITORY - Kulagina, Maria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The development of the subjects of the Russian Federation is not possible without financial resources. Altai Territory is traditionally a highly subsidized region. Currently, it is ranked 4th in terms of federal subsidies. Now, the Ministry of Finance of the Russian Federation orients the subjects of the federation towards increasing the independence and efficiency of functioning. The Central Bank of Russia is intensifying its bond issues and sees in this direction an effective way of replacing credit resources and bill circulation in the coming years. Currently, there are no comprehensive methods for generating informed decisions on the issue of sub-federal bonds. The purpose of this study is to formulate a method for making an informed decision on the issue of sub-federal bonds, based on an assessment of their potential. To achieve this purpose, the methods of economic and system analysis, synthesis, synthesis, empirical methods, methods of abstraction and analogies were used. The main results of the study include: forecasting changes in the Russian bond market in the future based on a comprehensive assessment of the Russian ruble bond market; a critical assessment of the effectiveness of the use of bond instruments by constituent entities of the Russian Federation, the author’s proposed system of key indicators that allow an objective assessment of the potential of sub-federal bonds, as well as a method for forming a reasonable decision on the timeliness and feasibility of issuing bonds by a subject of the federation. The proposed method was tested on the example of the Altai Territory.